Clinical Validation of an Office-Based (14)C-UBT (Heliprobe) for H. pylori Diagnosis in Iranian Dyspeptic Patients - Mansour-Ghanaei, Fariborz (Hindawi Publishing Corporation, 2011)
Background. We encountered repeatedly, in our clinical practice, discordant results between UBT and histopathology about H. pylori infection. Goal. To study the diagnostic accuracy of Heliprobe (14)C-urea breath test ((14)C-UBT) for detection of H. pylori infection in an Iranian population. Study. We enrolled 125 dyspeptic patients in our study. All of them underwent gastroscopy, and four gastric biopsies (three from the antrum and one from the corpus) were obtained. One of the antral biopsies was utilized for a rapid urease test (RUT), and three others were evaluated under microscopic examination. Sera from all patients were investigated for the presence of H. pylori IgG antibodies. The (14)C-UBT was performed on all subjects using Heliprobe kit, and results were analyzed against the following gold standard (GS): H. pylori infection considered positive when any two of three diagnostic methods (histopathology, RUT, serology) are positive. Results. According to data analysis, the Heliprobe (14)C-UBT had 94% sensitivity, 100% specificity, 93% negative predictive value (NPV), 100% positive predictive value (PPV), and 97% accuracy, compared with GS. Conclusion. The Heliprobe (14)C-UBT is an easy-to-perform, rapid-response, and accurate test for H. pylori diagnosis, suitable for office use.